Analysis of Minister of Social Affairs Regulation No. 01 of 2018 on PKH in Sungkai Tengah - Adhitama, Sam; Dwiono, Sugeng (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the role of Sungkai Tengah Subdistrict in the distribution of social assistance under the Family Hope Program (PKH) based on the Minister of Social Affairs Regulation No. 01 of 2018. The research focuses on the mechanisms employed by the subdistrict to ensure effective, efficient, and targeted distribution of assistance to eligible families. Additionally, the study examines the legal constraints faced by the subdistrict in implementing the program, including challenges in data verification and validation, limited access to financial institutions, and issues related to transparency and accountability in the distribution process. By employing a qualitative approach, this research highlights the importance of good governance principles, such as transparency, accountability, participation, and effectiveness, in enhancing the distribution of social assistance. The findings indicate that while Sungkai Tengah Subdistrict has made significant efforts to implement these principles, there are still considerable challenges that need to be addressed to improve the overall effectiveness of the PKH program. Recommendations for future improvements include enhancing public awareness of complaint mechanisms and leveraging technology to streamline verification and distribution processes. Ultimately, this study contributes to a better understanding of the role of local governance in social assistance distribution and aims to strengthen public trust in government programs.